Metastable Systems under Pressure - Rzoska, Sylwester; Drozd-Rzoska, Aleksandra; Mazur, Victor; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2010)
The fundamental insight and the technological & environmental relevance of metastable systems have given a strong impetus from the last decade development of extreme pressures experimental techniques, from the GPa region to the challenging negative pressures domain. The ultimate verification of theoretical models and reliable equations for portraying basic properties for such systems seems to be possible only when including temperature and pressure paths. This volume presents a set of papers related to novel findings on the glass transition phenomenon, phase transitions in liquid crystals, critical mixtures, bioliquids, geophysical system which can reveal surprising "secret" features only when using extreme pressures. This can be illustrated by the link between colloidal and molecular glassformers, the universal onset of the non-trivial dynamics in glasses, demistification of the secondary relaxation or novel findings associated with liquid - liquid near critical transitions in critical mixture, liquid crystals and in one component liquid, including water Particularly noteworthy is the emerging possibility of applications in geophysical and environment- relevant system as well as in technological application from material engineering, pharmacy industry, to biotechnology.
Supercooled, glassy system -- The Nature of Glass: Somethings Are Clear -- The Link Between the Pressure Evolution of the Glass Temperature in Colloidal and Molecular Glass Formers -- Evidences of a Common Scaling Under Cooling and Compression for Slow and Fast Relaxations: Relevance of Local Modes for the Glass Transition -- Reorientational Relaxation Time at the Onset of Intermolecular Cooperativity -- Neutron Diffraction as a Tool to Explore the Free Energy Landscape in Orientationally Disordered Phases -- A Procedure to Quantify the Short Range Order of Disordered Phases -- Consistency of the Vogel $1 (BFulcher $1 (BTammann (VFT) Equations For The Temperature-, Pressure-, Volume-and Density- Related Evolutions of Dynamic Properties in Supercooled and Superpressed Glass Forming Liquids/Systems -- Liquid crystals -- Stability and Metastability in Nematic Glasses: a Computational Study -- Phase Ordering in Mixtures of Liquid Crystals and Nanoparticles -- Anomalous Decoupling of the dc Conductivity and the Structural Relaxation Time in the Isotropic Phase of a Rod-Like Liquid Crystalline Compound -- Near-critical mixtures -- An Optical Brillouin Study of a Re-Entrant Binary Liquid Mixture -- New Proposals for Supercritical Fluids Applications -- 2D and 3D Quantum Rotors in a Crystal Field: Critical Points, Metastability, and Reentrance -- Water and liquid-liquid transitons -- Metastable Water Under Pressure -- Critical Lines in Binary Mixtures of Components with Multiple Critical Points -- About the Shape of the Melting Line as a Possible Precursor of a Liquid-Liquid Phase Transition -- Disorder Parameter, Asymmetry and Quasibinodal of Water at Negative Pressures -- Experimental Investigations of Superheated and Supercooled Water (Review of Papers of the School of the Academician V. P. Skripov) -- Estimation of the Explosive Boiling Limit of Metastable Liquids -- Lifetime of Superheated Water in a Micrometric Synthetic Fluid Inclusion -- Explosive Properties of Superheated Aqueous Solutions in Volcanic and Hydrothermal Systems -- Vapour Nucleation in Metastable Water and Solutions by Synthetic Fluid Inclusion Method -- Method of Controlled Pulse Heating: Applications for Complex Fluids and Pol Ymers -- Other metastable systems -- Collective Self-Diffusion in Simple Liquids Under Pressure -- Thermal Conductivity of Metastable States of Simple Alcohols -- Transformation of the Strongly Hydrogen Bonded System into van der Waals one Reflected in Molecular Dynamics -- Effects of Pressure on Stability of Biomolecules in Solutions Studied by Neutron Scattering -- Generalized Gibbs' Thermodynamics and Nucleation-Growth Phenomena -- Self-Assembling of the Metastable Globular Defects in Superheated Fluorite-Like Crystals -- Study of Metastable States of the Precipitates in Reactor Steels Under Neutron Irradiation -- Dynamics of Systems for Monitoring of Environment.s
Keywords: Physics; Geography; Planetology; Engineering; Physics; Soft and Granular Matter, Complex Fluids and Microfluidics; Complexity; Applied Earth Sciences; Solid State Physics; Spectroscopy and Microscopy; Planetology